The Impact Of Adopting The Social Responsibility On Marketing Performance An Applied Study on NAFTAL Company - Omar, BENDJIMA; Larbi, BENLAKHDAR Mohamed; Zakariya, NEFFAH (Journal of Economics and Administrative Sciences, 2020)
This research paper aims at studying the effect of adopting the corporate social responsibility on marketing performance indicators, where the study adopted the descriptive method for theoretical concepts, in addition to the statistical approach by using the SPSS v25 program to analyze the questionnaire and test the hypotheses of the study. The results showed that there is a positive correlation between social responsibility and marketing performance indicators, and the study found that it is better for NAFTAL Company to mix the environmental and social responsibilities in order to improve its marketing performance. Also, the study recommended that Naftal should adopt the four responsibilities equally, correctly and make its workers more aware of environmental and social responsibility through establishing it as a belief in its mission and vision, in order to gain a global position.